2003
DOI: 10.1002/pd.602
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of de novo terminal deletion of chromosome 7q

Abstract: Fetuses with a de novo 7q terminal deletion may be associated with a markedly elevated maternal serum hCG level and abnormal sonographic findings of intrauterine growth restriction, microcephaly, and congenital heart defects in the second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…The parents' decision is important in emphasizing the significance of prenatal diagnosis and genetic counseling. In a very recent report, we noticed prenatal diagnosis of a 7q terminal deletion associated with markedly elevated maternal serum free ß-human chorionic gonadotropin [18]. The pregnancy was also terminated, like the current case.…”
Section: Discussionmentioning
confidence: 82%
“…The parents' decision is important in emphasizing the significance of prenatal diagnosis and genetic counseling. In a very recent report, we noticed prenatal diagnosis of a 7q terminal deletion associated with markedly elevated maternal serum free ß-human chorionic gonadotropin [18]. The pregnancy was also terminated, like the current case.…”
Section: Discussionmentioning
confidence: 82%
“…Combined screening revealed a significantly diminished PAPP-A level (0.17 MoM) and a correspondingly high risk of DS (1: 50) which led to subsequent amniocyte karyotype evaluation. Chen et al [16] described a similar detection of a terminal chromosome 7q deletion, 46,XX,del(7)(q35), with the help of routine second-trimester DS screening. According to their report, 18 weeks' biochemical screening revealed a normal ␣ -fetoprotein level (1.026 MoM) but a markedly elevated free ␤ -hCG level (8.678 MoM) that led to a high risk of DS (1: 11) [16] .…”
Section: Discussionmentioning
confidence: 93%
“…Chen et al [16] described a similar detection of a terminal chromosome 7q deletion, 46,XX,del(7)(q35), with the help of routine second-trimester DS screening. According to their report, 18 weeks' biochemical screening revealed a normal ␣ -fetoprotein level (1.026 MoM) but a markedly elevated free ␤ -hCG level (8.678 MoM) that led to a high risk of DS (1: 11) [16] . Similarly to our case, the pregnancy was terminated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We tested this subgroup because SHD might be part of a syndromal disorder, or associated with as yet unknown genetic defects [37] , which might interfere with growth. For example, several genetic defects like the 22q11 [38] or deletion of 7q [39] have only recently been identified. It seems of practical interest to note that in the present study the severely growth-retarded patients with CHD showed the same response to GH as all other patients born SGA.…”
Section: Discussionmentioning
confidence: 99%